Counteracting Roles of Lipidic Aldehydes and Phenolic Antioxidants on Soy Protein Oxidation Defined by a Chemometric Survey of Solvent and Mechanically Extracted Soybean Meals - Junwei Zhang; Pedro E. Urriola; Seth L. Naeve; Gerald C. Shurson; Chi Chen (MDPI AG, 2023)
Soybean meal (SBM) is a premier source of protein for feeding food-producing animals. However, its nutritional value can be compromised by protein oxidation. In this study, a total of 54 sources of solvent extracted SBM (SSBM) and eight sources of mechanically extracted SBM (MSBM), collected from different commercial producers and geographic locations in the United States during the years 2020 and 2021, were examined by chemometric analysis to determine the extent of protein oxidation and its correlation with soybean oil extraction methods and non-protein components. The results showed substantial differences between SSBM and MSBM in the proximate analysis composition, protein carbonyl content, lipidic aldehydes, and antioxidants, as well as subtle differences between 2020 SSBM and 2021 SSBM samples in protein oxidation and moisture content. Correlation analysis further showed positive correlations between protein carbonyl content and multiple lipid parameters, including the ether extract, p-anisidine value, individual aldehydes, and total aldehydes. Among the antioxidants in SBM, negative correlations with protein carbonyl content were observed for total phenolic content and isoflavone glycoside concentrations, but not for Trolox equivalent antioxidant capacity (TEAC), α-tocopherol, and γ-tocopherol. Overall, soybean oil extraction methods, together with other factors such as enzyme treatment and environmental conditions, can significantly affect the proximate analysis composition, the protein and lipid oxidation status, and the antioxidant profile of SBM. Lipidic aldehydes and phenolic antioxidants play counteracting roles in the oxidation of soy protein. The range of protein carbonyl content measured in this study could serve as a reference to evaluate the protein quality of SBM from various sources used in animal feed.